Macelignan inhibits bee pathogenic fungi Ascophaera apis growth through HOG1 pathway - Y.K. Shin (Brazilian Journal of Medical and Biological Research, 2016)
Ascosphaera apis is a bee pathogen that causes bee larvae infection disease, to which treatment is not yet well investigated. The aim of this study was to investigate antifungal susceptibility in vitro against A. apis and to identify a new antifungal agent for this pathogen through minimal inhibitory concentration (MIC) assay and western blot analysis. Macelignan had 1.56 and 3.125 μg/mL MIC against A. apis after 24 and 48 h, respectively, exhibiting the strongest growth inhibition against A. apis among the tested compounds (corosolic acid, dehydrocostus lactone, loganic acid, tracheloside, fangchinoline and emodin-8-O-β-D-glucopyranoside). Furthermore, macelignan showed a narrow-ranged spectrum against various fungal strains without any mammalian cell cytotoxicity. In spite of miconazole having powerful broad-ranged anti-fungal activity including A. apis, it demonstrated strong cytotoxicity. Therefore, even if macelignan alone was effective as an antifungal agent to treat A. apis, combined treatment with miconazole was more useful to overcome toxicity, drug resistance occurrence and cost effectiveness. Finally, HOG1 was revealed as a target molecule of macelignan in the anti-A. apis activity by inhibiting phosphorylation using S. cerevisiae as a model system. Based on our results, macelignan, a food-grade antimicrobial compound, would be an effective antifungal agent against A. apis infection in bees.